PIBID: sua contribuição na constituição docente - Zanetti, Pamela Nadai Guisantez [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
This study aimed to systematize and analyze the scientific production that deals with Pibid's contribution to the teaching constitution of future teachers Pedagogy. The research aimed to analyze the formative implications of the inserting of the fellows at school, at my specific inserting and identify in the records produced by me during the years 2014-2015 and 2016, elements that indicate the knowledge produced in the school context. For this, I developed a qualitative research, from an autobiographical methodological perspective, and using as data instruments of production records produced during my participation in subproject Pibid Literature of the contribution in the formative processes in the school context in the 2014 period to 2016. Furthermore I did bibliographic survey in the Annals of Educere, XII Congress of Education (2015) and in the Annals of ANPEd (National Association of Graduate Studies and Research in Education (2015). This research indicates that the PIBID has been contributing to the production of knowledge of experience theoretically grounded, qualifying the constitution of the future teacher of Pedagogy, which thus entails implications on the concepts of education and transformation of it and society

O presente trabalho objetivou sistematizar e analisar a produção científica que trata da contribuição do Pibid para a constituição docente dos futuros professores de Pedagogia. A pesquisa objetivou analisar as implicações formativas da inserção dos bolsistas na escola, em especifico a minha inserção, e identificar nos registros produzidos por mim durante os anos de 2014-2015 e 2016, elementos que indiciem os saberes produzidos no contexto da escola. Para isso, desenvolvi uma pesquisa de abordagem qualitativa, partindo de uma perspectiva metodológica autobiográfica, e utilizando como instrumentos de produção de dados os registros produzidos durante minha participação no subprojeto Pibid A contribuição da literatura nos processos formativos no contexto escolar no período de 2014 a 2016. Além disso, fiz levantamento bibliográfico nos Anais do EDUCERE, XII Congresso Nacional de Educação (2015) e nos Anais da ANPEd (Associação Nacional de Pós-Graduação e Pesquisa em Educação (2015). Esta pesquisa indicia que o PIBID tem contribuído para a produção de saberes da experiência embasados teoricamente, qualificando a constituição do futuro professor de Pedagogia, que, deste modo, traz implicações nas concepções de educação e na transformação da mesma e da sociedade
Keywords: Professores - Formação; Escrita; Educação; Freinet, Metodo de educação; Teachers, Training of